UNDERSTANDING RISK PERCEPTION AND RISK TOLERANCE AMONG VACCINE REFUSERS IN BANDUNG: A CASE STUDY OF RISK COMMUNICATION DURING THE COVID-19 PANDEMIC - Adiputra, Andika Vinianto; Sjuchro, Dian Wardiana; Suminar, Jenny Ratna; Kheokao, Jantima (PT Altin Riset Publishing, 2025)
Public rejection and hesitation towards vaccination continue to increase. Based on data from the West Java Provincial Health Office, various obstacles hinder vaccination coverage in the region. This study aims to identify and analyze the factors that influence people's risk perception and risk tolerance in making decisions related to vaccination during the COVID-19 pandemic, especially in Bandung City, the largest city in West Java. This research uses a qualitative method with a constructivist paradigm and a case study approach. The research subjects consisted of 12 Bandung residents who refused or hesitated to vaccinate and were selected through a purposive sampling technique. Primary data was obtained through in-depth interviews, while secondary data was collected from documentation studies, literature, and other supporting sources. The results showed that risk perception towards vaccination is influenced by several aspects, such as underestimating the danger of the virus and distrusting the government, lack of understanding about the virus and vaccines, belief in the haram status of vaccines and conspiracy theories, personal experiences related to negative impacts on loved ones or livelihoods, and concerns about side effects and vaccine effectiveness. Meanwhile, risk tolerance is influenced by subjective and socioeconomic aspects. These factors play a major role in the lack of changes in health behavior in the future, especially in decisions related to vaccination.